Residual effects of four pesticides on the predatory bug, Orius albidipennis Reut. (Hem.: Anthocoridae). (14th June 2016) - Kosari, Ali Asghar; Fazeli-Dinan, Mahmoud
Abstract: Residual effects of abamectin (0.02%), propargite (0.1%), dichlorvos (DDVP) (0.15%) and pymetrozine (0.15%) were determined on Orius albidipennis at laboratory conditions. Planted cucumbers were sprayed with the highest recommended concentrations of all insecticides and experimental treatments were monitored during 20 days based on the period of pesticides residues. On the first day after spraying, the greatest of mortality belonged to dichlorvos and pymetrozine (97 ± 1.22, 57 ± 3.1, respectively, p < 0.01), while abamectin and propargite had the highest mortality after four (44 ± 1.87 and 24 ± 2.91, respectively, p < 0.01) and eight (51 ± 2.91 and 17 ± 2.23, respectively, p < 0.01) days after spraying. At day 16th, post treatment, abamectin had the highest residual mortalities on O. albidipennis (15 ± 1.58, p < 0.01) and finally mortality results at the 20th day showed there is no significant difference between insecticides ( p < 0.01).